Oral Status and Its Relationship With Quality of Life Among Vietnamese Students - Thuy Anh Vu Pham; Vu Pham Phi Nguyen; Chau Tran Bao Vu; Khoa Le Doan; Nhi Thi Thuc Nguyen; Phong Phu Le (International Journal of Dentistry)
Conclusion: This study showed that students’ perception of quality of life was at a good level. The prevalence of participants with dental caries was classified as moderate. There was a clear relationship between the mean total OHIP-14VN index and the specific component factors of OHIP-14VN, with tooth loss and periodontal indicators.